RADHIYAH KHATUN THE FIRST MUSLIM WOMAN RULER - Mohtaram Vakili Sahar (تاریخ اسلام, 2006)
Delhi, the most important city in northern India, was constructed by Rajah Prithvi and is the oldest of the seven cities attributed to this name. Because of its strategic position, many dynasties ruled Delhi the most important of which were the Sultans of Delhi. One major branch of the Sultans of Delhi dynasty was the “Shamsiyan of India”. Radhiyah Khatun was the fifth king of this branch and the first Muslim woman to ascend the throne. She ruled independently for four years (634-638 A.H.) in Delhi and embarked on reforms in different areas. How Radhiyah Khatun took power, the major events of her rule, and her end are issues dealt with in this paper.